2017
DOI: 10.1002/lary.26959
|View full text |Cite
|
Sign up to set email alerts
|

Process of tight junction recovery in the injured vocal fold epithelium: Morphological and paracellular permeability analysis

Abstract: NA. Laryngoscope, 128:E150-E156, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…34,35 The presence of these proteins in VF tissue has been described in rabbits, 36,37 pigs, 38 and sheep, 39 but the distribution of these proteins has only been localized to the epithelium of rat VFs. 15 Similar to these findings in rats, our study found that ZO-1 and occludin were localized to the rabbit and human epithelium. There was also substantial ZO-1 labeling in the superficial LP of both species, but only substantial occludin labeling in the superficial LP of rabbit samples.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…34,35 The presence of these proteins in VF tissue has been described in rabbits, 36,37 pigs, 38 and sheep, 39 but the distribution of these proteins has only been localized to the epithelium of rat VFs. 15 Similar to these findings in rats, our study found that ZO-1 and occludin were localized to the rabbit and human epithelium. There was also substantial ZO-1 labeling in the superficial LP of both species, but only substantial occludin labeling in the superficial LP of rabbit samples.…”
Section: Discussionsupporting
confidence: 84%
“…13 Cell-cell adhesion and tight junction molecules such as E-cadherin, ZO-1, and occludin, have been more extensively studied across various animal species and humans, but the localization of this integral cell adhesion protein in animals has not been directly compared to humans. [14][15][16] Although the aforementioned integral membrane proteins have been explored in various animal models, the identification and localization of these proteins has not been localized in rabbit and compared to human VFs. The purpose of the current study was to identify the localization of AQP1, AQP4, AQP7 Na+/K + -ATPase, E-cadherin, ZO-1, and occludin in rabbit and human VFs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, results of our immunoblotting analysis ( Figure 4 ) showed that MI condition significantly increased the expression of claudin-1, occludin, and zo-1 proteins in the small intestine when compared to normal rats. Claudin-1, occluding and zo-1 belong to the family of proteins that are the most important components of the TJs, where they establish the paracellular barrier that controls the flow of hydrophilic small molecules in the intercellular space between intestinal epithelial cells ( Suzuki et al, 2017 ). Thus, we hypothesized that the poorer permeability through the intestinal epithelial membrane is more likely to be responsible for the decreased values of T max , AUC 0–t , and C max of GA after MI.…”
Section: Resultsmentioning
confidence: 99%
“…This type of vocal fold injury would translate to clinical practice as a type II cordectomy (subligamental cordectomy). The vocal fold stripping model is a well-established first step to address the complex nature of EMC modifications, vocal fold scarring, and fibrosis using various solutions from tissue engineering to stem cells, growth factors, and antifibrotic agents [ 10 12 , 15 , 18 , 19 , 23 , 24 ]. Instrumentation tends to be similar, using small gauge needles for the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscope size ranged from 1.9 mm to 2.7 mm. Endoscope angle was 25–30 degrees in most cases [ 11 , 12 , 14 , 15 , 18 ] and 0 degrees only in 2 cases [ 9 , 16 ]. Proper visualization is essential, and the 25–30s degree, small diameter endoscopes provide the best angle and room for manipulation.…”
Section: Discussionmentioning
confidence: 99%